Experimental Research on the Bearing Properties of Red Mud Geopolymer Foundations - Zhang, Haiqing; Qin, Lusheng; Nie, Qingke; Wang, Yinghui; Jia, Xiangxin (Frontiers in Earth Science, 2022)
In this study, the mechanical properties of composite foundations in red mud ground were examined, and the reinforcement effect of composite foundation dams with mixed geopolymer piles of fly ash and red mud were determined. The feasibility of red mud geopolymers as pile materials for composite foundations was verified by laboratory and field tests. The static load test of the red mud geopolymer foundation showed that the effective length of the pile body in the red mud foundation is approximately 8 m, and the stress of the soil layer is generally limited within 2 m below the ground surface. The results also showed that the principal load is supported by the pile body, while the bearing capacity of this kind of foundation is mainly provided by the side friction of the pile. The bearing mechanism of the new foundation is similar to that of conventional mixed composite ground. This is of great significance to optimize the red mud geopolymer foundation design and maximize the use of the pile bearing properties. Overall, there is a positive role in promoting the development of red mud dam reinforcement technology.